The effect of centre-elevator on aerodynamics of UiTM baseline-1 blended wing body (BWB) unmanned aerial vehicle (UAV) at low subsonic speed / Rizal Effendy Mohd Nasir .. [et al.] - Mohd Nasir, Rizal Effendy (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2009)
A group of researcher in Universiti Teknologi MARA (UiTM) has started a project on the development of future unmanned aerial vehicle based on BWB concept since 2005. A case study on the effect of centre-elevator deflection to aerodynamics of UiTM's Baseline-1 blended wing-body aircraft is presented in this paper. Elevator deflection in study is limited to ± 10 degrees. Analytical theory on possible contribution of elevator deflection to aerodynamic coefficients is highlighted. Aerodynamic parameters are computed via computational fluid dynamics method based on RANS to simulate low subsonic flight at Mach 0.3 sea level ISA. Discussions focus on the effect of elevator deflection to lift, drag and moment curves at small angles of attack within linear region ofCL-α curve. Results show significant change in lift and drag coefficients within + 10 degrees elevator deflection but no considerable change of moment that it is impossible to change trim angle of attack without shifting centre of gravity.